Composition of the Essential Oil of Endemic Centaurea paphlagonica (Bornm.) Wagenitz From Turkey - Bulent Kose, Y.; Altintas, Ayhan; Demirci, Betul; Celik, Sezgin; Can Baser, K.H. (Asian Journal of Chemistry, 2010)
The essential oil obtained by hydrodistillation from endemic Centaurea paphlagonica (Asteraceae) in Plumosipappus (Czerep.) Wagenitz section from Turkey was analyzed by gas chromatography and gas chromatography/ mass spectrometry, simultaneously. Main constituents of the oil were found as hexadecanoic acid (28.9 %), dodecanoic acid (22.8%) and caryophyllene oxide (9.2 %). Fatty acids were identified as the main constituent groups of the species.